Toward Resilience City: Potential Hazards and Scenario for Ternate Island, North Maluku - Mohammad Ridwan Lessy; Nani Nagu; Fais Nurul Hadi (TECHNO: JURNAL PENELITIAN, 2024)
Natural hazards and climate change significantly threaten almost every small island. This is due to the small island's isolation and lack of resources. Ternate Island is a small island that is now afflicted by this issue. Geographically, the island is surrounded by active plates and volcanic paths, making it at risk of serious catastrophes. Population growth and limited land resources also contribute to a high disaster susceptibility. We characterize the features of the small island of Ternate by classifying the types of disasters that threaten it based on a literature database. Earthquakes, volcanic eruptions, floods, extreme weather events, and tsunamis are natural disasters that occur often in Ternate. Additionally, these findings indicate the significant importance of a multi-hazard approach to disaster response. Our examination concludes with some recommendations for establishing the resilience of Ternate City.